2005
DOI: 10.1152/ajpheart.01129.2004
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-related heart rate variability in progressive experimental heart failure

Abstract: Entee. Respiratory-related heart rate variability in progressive experimental heart failure. Am J Physiol Heart Circ Physiol 289: H1729 -H1735, 2005. First published May 27, 2005; doi:10.1152/ajpheart.01129.2004.-Heart failure is associated with autonomic imbalance, and this can be evaluated by a spectral analysis of heart rate variability. However, the time course of low-frequency (LF) and high-frequency (HF) heart rate variability changes, and their functional correlates during progression of the disease are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 35 publications
2
31
1
1
Order By: Relevance
“…Using the phenylephrine bolus technique, Eckberg et al [27] showed over 40 years ago that arterial baroreflex control of HR was reduced in patients with LV dysfunction. Since that time, numerous groups of investigators have used a variety of techniques to support these findings, including time and frequency domain measures of RR variability, spectral analysis of HR, HR recovery following exercise, HR turbulence, and spontaneous or provoked arterial baroreflex testing [4,28,29]. Moreover, altered vagal control of HR is apparent early in the development of LV dysfunction.…”
Section: Abnormal Vagal Control Of the Heartmentioning
confidence: 99%
“…Using the phenylephrine bolus technique, Eckberg et al [27] showed over 40 years ago that arterial baroreflex control of HR was reduced in patients with LV dysfunction. Since that time, numerous groups of investigators have used a variety of techniques to support these findings, including time and frequency domain measures of RR variability, spectral analysis of HR, HR recovery following exercise, HR turbulence, and spontaneous or provoked arterial baroreflex testing [4,28,29]. Moreover, altered vagal control of HR is apparent early in the development of LV dysfunction.…”
Section: Abnormal Vagal Control Of the Heartmentioning
confidence: 99%
“…In heart failure, loss of HRV is indicative of decreased cardiac vagal drive and an inability of the parasympathetic system to properly buffer elevated cardiac sympathetic drive, which contributes to ventricular arrhythmogenesis in CHF (42). In dogs subjected to pacing-induced heart failure, increased sympathetic drive to the heart is reflected by increased HRV in the LF domain in the early stages of the disease (36). However, with disease progression, LF oscillations in HR diminish, likely due to reduced sensitivity of cardiac ␤-receptors (4).…”
mentioning
confidence: 99%
“…HF waves are a marker of parasympathetic nervous activity, and LF waves are a marker of both sympathetic nervous activity and parasympathetic nervous activity. 6,8 The ratio of LF to HF (LF/HF) is defined as an indicator of sympathetic nervous activity.…”
mentioning
confidence: 99%
“…Several studies have been performed to assess HRV in several species such as humans, 3,7 dogs, 6 pigs, 9 calves, 10,11 rabbits, 12 and rats. 13,14 However, haemodynamic parameters are totally different in each animal, 15 -17 and optimal animal models for studying HRV corresponding to human HRV are still unclear.…”
mentioning
confidence: 99%